Leaving more than footprints: Anthropogenic nutrient subsidies to a protected area. Issue 12 (28th December 2022) - Guerra, A. S.; Bui, A.; Klope, M.; Orr, D. A.; Shaffer, S. A.; Young, H. S.
Abstract: Mobile animals that traverse ecosystem boundaries can fundamentally reshape environments by providing critical nutrient and energy inputs to the ecosystems they inhabit. In particular, aggregations of seabirds often transform coastal and island ecosystems through large amounts of nutrient‐rich guano deposition. Anthropogenically driven losses of these subsidies can occur through changes in abundance of mobile species, including seabirds, and have been shown to drive whole‐scale ecosystem state change on islands. However, even though many species that forage on anthropogenic food sources are highly mobile and may thus play important roles in moving nutrients from urban systems to otherwise conserved ecosystems, the impacts of anthropogenic supplements on spatial subsidies have been largely ignored. Here we examine the effects of large nesting colonies of Western Gulls ( Larus occidentalis ), a generalist carnivore known to forage on human refuse, on the Channel Islands of California. Specifically, we explore how their foraging on human subsidies may change nutrient deposition patterns at their relatively remote and protected breeding islands. We equipped gulls with GPS loggers to assess the frequency of urban foraging, and we partnered this tracking data with bird density data to estimate the rate of wild and urban‐derived guano deposition on two different islands. Consistent with research on other gull species, we found high (up to 40%) but island‐specific rates of urban foraging, resulting between 66 and 93 kg ha −1 of guano in these two sites during the breeding season, a level greater than half the amount of fertilizer applied annually in typical commercial agricultural settings and likely the primary source of nitrogen and phosphorus inputs to this system. Specifically, we estimate that 27 kg ha −1 year −1 of nutrient‐rich guano is shuttled to these otherwise isolated islands from anthropogenic sources. This research highlights the large shadow (i.e., footprint) that human activity can cast on even remote ecosystems by driving significant nutrient enrichment through impacts on animal behavior and connectivity.